2020
DOI: 10.1111/mmi.14656
|View full text |Cite
|
Sign up to set email alerts
|

H‐NS‐like proteins in Pseudomonas aeruginosa coordinately silence intragenic transcription

Abstract: The H‐NS‐like proteins MvaT and MvaU act coordinately as global repressors in Pseudomonas aeruginosa by binding to AT‐rich regions of the chromosome. Although cells can tolerate loss of either protein, identifying their combined regulatory effects has been challenging because the loss of both proteins is lethal due to induction of prophage Pf4 and subsequent superinfection of the cell. In other bacteria, H‐NS promotes the cellular fitness by inhibiting intragenic transcription from AT‐rich target regions, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 97 publications
(149 reference statements)
1
19
0
Order By: Relevance
“…With ATG 1503602 as putative start codon, olg2 spans 1728 nt and overlaps with two annotated genes. A region of 1536 nt is shared with PA1383, a hypothetical gene predicted to code for an N-terminal Type I signal sequence for cytoplasmic export 55 , which has been shown to be regulated by the transcriptional repressor NrdR 56 , and by both the repressors mvaT and mvaU 57 . Additionally, olg2 overlaps in frame +2 by 34 nt with the galE gene (PA1384), which encodes for a UDP-glucose 4-epimerase.…”
Section: Resultsmentioning
confidence: 99%
“…With ATG 1503602 as putative start codon, olg2 spans 1728 nt and overlaps with two annotated genes. A region of 1536 nt is shared with PA1383, a hypothetical gene predicted to code for an N-terminal Type I signal sequence for cytoplasmic export 55 , which has been shown to be regulated by the transcriptional repressor NrdR 56 , and by both the repressors mvaT and mvaU 57 . Additionally, olg2 overlaps in frame +2 by 34 nt with the galE gene (PA1384), which encodes for a UDP-glucose 4-epimerase.…”
Section: Resultsmentioning
confidence: 99%
“…Although this study identified the MvaU binding site as an AT-rich region within the phz2 promoter, subsequent foot-printing analysis failed to identify the specific MvaU binding sequence. Similarly, very few MvaU binding sites have been identified in other Pseudomonas strains [ 10 , 30 ]. These results are probably due to the unique characteristics of MvaU.…”
Section: Discussionmentioning
confidence: 99%
“…MvaU is a small transcriptional regulator without the typical helix-turn-helix (HTH) DNA binding domain. MvaU typically acts as a gene silencer and regulates the expression of more than 300 genes [ 10 , 11 ]. Its binding to DNA requires specific co-factors or unique in vivo conditions that warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pseudomonas phage LUZ24 encodes an "early protein," gp4, that binds the H-NS family protein MvaT (36). MvaT is thought to play an important role in the genome organization of P. aeruginosa and in the regulation of gene transcription (15,37). The fold architecture of the MvaT monomer consists of an a-helical N-terminal oligomerization domain (NTD: residues 1-64) tethered to a C-terminal DNA binding domain (DBD) (residues 79-124) by a flexible linker (residues 65-78) ( Figure S1b) (18).…”
Section: Introductionmentioning
confidence: 99%